2010
DOI: 10.1161/atvbaha.110.204859
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteocalcin Is Associated With Measures of Insulin Resistance, Adipokine Levels, and the Presence of Metabolic Syndrome

Abstract: Objective-Osteocalcin has been reported to influence insulin secretion in experimental animals. We investigated whether serum osteocalcin was associated with measures of insulin resistance, circulating adipokine levels, and the presence of metabolic syndrome (MetSyn). Methods and Results-Serum osteocalcin was measured by solid-phase sandwich immunoassay in 1284 blacks (64Ϯ9 years; 71% women) and 1209 non-Hispanic whites (59Ϯ10 years; 57% women) belonging to hypertensive sibships. MetSyn was defined per Adult T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
146
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(170 citation statements)
references
References 27 publications
20
146
1
3
Order By: Relevance
“…A total of 1,284 Afro-Americans and 1,209 non-Hispanic whites individuals were evaluated and, in both populations, osteocalcin was inversely related to leptin and metabolic markers, such as body mass index, waist circumference, blood glucose, insulin and triglycerides, and directly related to adiponectin. In this study, the worse the severity of the metabolic syndrome the lower levels of osteocalcin were found, independently of the glycemic changes (33). More recently, Bao and cols.…”
Section: Osteocalcin Levels and Metabolic Parameters In Humanssupporting
confidence: 64%
See 1 more Smart Citation
“…A total of 1,284 Afro-Americans and 1,209 non-Hispanic whites individuals were evaluated and, in both populations, osteocalcin was inversely related to leptin and metabolic markers, such as body mass index, waist circumference, blood glucose, insulin and triglycerides, and directly related to adiponectin. In this study, the worse the severity of the metabolic syndrome the lower levels of osteocalcin were found, independently of the glycemic changes (33). More recently, Bao and cols.…”
Section: Osteocalcin Levels and Metabolic Parameters In Humanssupporting
confidence: 64%
“…A large observational study correlated osteocalcin levels with adipokines (leptin and adiponectin) and markers of metabolic syndrome, body fat and physical activity (33). A total of 1,284 Afro-Americans and 1,209 non-Hispanic whites individuals were evaluated and, in both populations, osteocalcin was inversely related to leptin and metabolic markers, such as body mass index, waist circumference, blood glucose, insulin and triglycerides, and directly related to adiponectin.…”
Section: Osteocalcin Levels and Metabolic Parameters In Humansmentioning
confidence: 99%
“…Higher levels of osteocalcin were also associated with a lower odds ratio of developing metabolic syndrome in black and in white nonHispanic individuals [29,38]. A case-control study actually identified coding variants in the fourth exon of human OCN that appeared to correlate with type 2 diabetes in AfricanAmerican patients [39].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…A fast growing number of studies, however, have now established that multiple aspects of osteocalcin biology are similar in rodents and humans. Indeed, levels of circulating osteocalcin have been inversely correlated with BMI, fat mass and plasma glucose levels in adult or elderly men and women of diverse ethnicities [26][27][28][29]. Additional studies have linked low osteocalcin to impaired levels of HbA 1c , fasting insulin and insulin resistance (estimated by the HOMA of insulin resistance HOMA-IR) in adult men and women, irrespective of whether they have diabetes [28,[30][31][32][33].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…After the observation of reduced insulin secretion and increased insulin resistance in Osteocalcin-deficient mice, serum osteocalcin level was found to be associated with HbA1c and type II diabetes in humans (13). On this basis, the implication of osteocalcin in humans was then extended to MetS (14,15). Most of the available studies have reported an association between osteocalcin and the absence/presence of MetS.…”
Section: Introductionmentioning
confidence: 99%